The reliability and validity of the arthritis impact measurement scales 2-short form adapted for Filipino patients with osteoarthritis - Alviar, Maria Jenelyn M.
OBJECTIVES: To develop a cross-cultural adaptation of the Arthritis Impact Scales 2-Short Form (AIMS2-SF) for Filipino patients with Osteoarthritis; and to determine its reliability and validity. To determine the quality of life (QOL) of Filipino patients with osteoarthritis according to the five domains specified in the cross-cultural adaptation of the AIMS2-SF. To determine the relationship of the socio-demographic and clinical characteristics with the quality of life. DESIGN: Cross-sectional. METHODOLOGY: A. Development of the AIMS-2SF Filipino version: A cross-cultural adaptation of the Arthritis Impact Measurement Scales 2-Short Form, "Pagsukat ng Kalagayan ng Pasyente na may Arthritis", was developed by forward/backward translation, committee review and pre-testing. B. Tests of reliability and validity: Three hundred patients with osteoarthritis as per ACR criteria seen in the Rehabilitation Medicine Out-patient Departments of Philippine General Hospital and Jose Reyes Memorial Medical Center were included in the study. Socio-demographic (age, sex, status, occupation, education attainment, income) and clinical variables (joint/s affected, area of involvement, visual analog scale score (VAS), duration of symptoms, number of painful joints, grip strength, walk time, number of co-morbid conditions) were recorded. The Filipino version of the AIMS-2 SF was administered to all subjects. Inter-item reliability, item-to-total reliability, and internal consistency analyses were performed. Content validity (content relevance and content coverage) was assessed by a panel of content experts. Convergent validity was evaluated by testing a priori-hypotheses. Construct validity was assessed by factor analysis.
The cross-cultural adaptation of the AIMS2-SF, "Pagsukat ng Kalagayan ng Pasyente na may Arthritis", has a 5-domain structure (physica / function, pain / symptom, affect, social role / work) with 26 items (Physical domain: Items P1-P12; Symptom domain: Items S1-S3; Affect domain: Items A1-A5; Social Relations domain: Items SR1-SR4; work domain: Items W1-W2). The tool adhered to conceptual, item, semantic, operational, measurement equivalence. Internal consistency (Cronbach alpha) was moderate / good in all scales (0.65 - 0.77) except the social scale (0.40). Content validity (content relevance and content adequacy) was fair as per content experts assessment. Pearson's correlation coefficients were statistically significant for 8 out of the 10 a prior-hypotheses generated: (1) The AIMS2-SF (Filipino version) Pain / Symptom (r=-0.376, p<0.001) and Physical/Function Scores (r=-0.246, p<0.001) were negatively associated with patient VAS Scores; (2) The Physical/Function Scores were negatively associated with the number of tender, swollen joints (r=0.315, p<0.001); (3) The Physical/Function Scores were negatively associated with the walk time if affected joints were lower extremities and lumbosacral area (r=-0.485, p<0.001); (4) The Pain (r=0.152, p<0.008) and Physical function Scores (r=0.373, p<0.001) were positively associated with the grip strength if the affected joints were supper extremities and cervical spine; (5) The total QOL scores showed no association with the number of co-morbidities r=-0.112, p=0.054) and duration of symptoms (r=-0.085, p=0.141). Factor analysis identified five major factors corresponding to the scales of the tool, with the items on the physical / function scale being represented by two separate factors suggesting that upper body activities should be distinguished from lower body activities. The average scores for the five domains namely: physical / function, pain / symptom, affect, social and role / work were 7.41, 5.52, 6.26, 5.41 and 5:30 respectively. The mean scores of the oestoarthritic patients for the pain / symptom, role / work, and social factors were relatively lover compared to the physical and social factors. Multiple linear regression showed that the QOL scores was related to sex (B=-3.373, 95% CI{-5.283-1.464}), pain severity (VAS) (b=-0.788, 95% ci {-1.603-0.513}), walk time (B=0.067, 95% CI {-0.095-0.039}), grip strength(B=0.228, 95% CI {0.139-0.317}), education (B=1.87, 95% CI {0.064-3.683}) and income (B=0.0001, 95% CI {0.00004-0.00020}).The tool, "Pagsukat sa Kalagayan ng Pasyente na may Arthrities" is a cross-cultural of the AIMS2-SF developed with adherence to conceptual, item, semantic, operational, and measurement equivalence. It has 5-component structure (physica / function, pan / symptom, affect, social, role / work) with 26 items. It is a reliable and valid tool for assessing health status in adult Filipino patients with osteoarthrits. The relatively lower QOL scores in the pain / symptom, role / work and social domains suggest that osteoarthritis affects patients considerably in these aspects. The relatively higher mean score for the physical component hints that osteoarthritic patients, in general, have lesser physical impairments and thus, are still functional and capable of doing activities of daily living. The comparatively higher average score for the affect scale reflects a trait of Filipinos, that of lightheartedness, which is a face-saving mechanism in the Filipino culture, especially during periods of distress and suffering. In this study, there is an association between sex, pain severity, walk time, grip strength, education and income with the total QOL score is associated with female sex, higher grip strength, higher income and higher level of education. QOL score is higher with decreased pain severity and decreased walk time.
Vita.
Thesis (MS Clinical Epidemiology)--University of the Philippines Manila
Keywords: Arthritis